Effects of Mitragynine and a Crude Alkaloid Extract Derived from Mitragyna speciosa Korth. on Permethrin Elimination in Rats - Kachamas Srichana; Benjamas Janchawee; Sathaporn Prutipanlai; Pritsana Raungrut; Niwat Keawpradub (MDPI AG, 2015)
Detoxification and elimination of permethrin (PM) are mediated by hydrolysis via carboxylesterase (CES). Mitragyna speciosa (kratom) contains mitragynine (MG) and other bioactive alkaloids. Since PM and MG have the same catalytic site and M. speciosa is usually abused by adding other ingredients such as pyrethroid insecticides, the effects of MG and an alkaloid extract (AE) on the elimination of PM were investigated in rats. Rats were subjected to single and multiple pretreatment with MG and AE prior to receiving a single oral dose (460 mg/kg) of PM. Plasma concentrations of trans-PM and its metabolite phenoxybenzylalcohol (PBAlc) were measured. The elimination rate constant (kel) and the elimination half-life (t1/2 el) of PM were determined, as well as the metabolic ratio (PMR). A single and multiple oral pretreatment with MG and AE altered the plasma concentration-time courses of both trans-PM and PBAlc during 8-22 h, decreased the PMRs, delayed elimination of PM, but enhanced elimination of PBAlc. Results indicated that PM-MG or AE toxicokinetic interactions might have resulted from the MG and AE interfering with PM hydrolysis. The results obtained in rats suggest that in humans using kratom cocktails containing PM, there might be an increased risk of PM toxicity due to inhibition of PM metabolism and elimination.